Yabancılara Türkçe Öğretiminde Etkinlikler - A1 - A2 - Er, Onur; Aramak, Kürşat; Özden, Esra; Yazıcı, Muhammet Hüseyin; Biçer, Nurşat; Memiş, Muhammet; Ertürk, Berker; Çıvğın, Hakan; Işık Kobazi, Ayşegül; Yılmaz Karaca, Meryem; İşci Karameşe, Cenan and Çetin, Betül and Aktaş, Tuğba and Yusufoğlu, Sevda and Kocayanak, Dilek and Yıldız, Nurgül and Demirel, M. Volkan and Karacan, Yağmur and Bal, Mazhar and Çep, Melike Nur and Göktaş, Betül and Bağcı Ayrancı, Bilge and Aydın, Zeliha and Sarıköse, Mehmet and Özkan, Erdost and Atmaca, İrem Nur and Başkan, Ahmet and Yazıcı, Muhammet Hüseyin and Kara, Abdulkadir and İşci Karameşe, Cenan and Şengül, Ladin and Mercan, Öykü and Bağcı Ayrancı, Bilge and Aydın, Zeliha and Ünlücömert, Nurgül and Sıla Kara, Devrim and Başutku, Serdar (Academician Publishing Book DOI Portal, 2024)
-